Euro-American Esoteric Readings of East Asia: Introductory Remarks - Pokorny, Lukas K. (Numen, 2024)
This article introduces the special issue “Euro-American Esoteric Readings of East Asia.” First, the genesis of the special issue is explained, after which working definitions of the key terminology are given, namely, “East Asia,” “Euro-American,” “Western,” and “esotericism.” Next, the rationale of the special issue as well as short synopses of its five contributions are presented. The article argues that esoteric readings of things East Asia have saliently coshaped their Western reception history.